KREATIFITAS DALAM PEMBELAJARAN PAI: STRATEGI KOOPERATIF BERBASIS MIND MAPPING UNTUK MENINGKATKAN KONSENTRASI SISWA - Apriliani, Widia; Irma Soraya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mind Mapping is considered a suitable instructional approach for elementary education, as it aligns with the natural tendencies of young learners who are more engaged in interactive and enjoyable activities. In the context of Islamic Religious Education (PAI), a cooperative learning strategy integrated with Mind Mapping has been shown to enhance students’ concentration during lessons. This study aims to examine the effectiveness of this approach in improving students’ focus at SD TAQUMA Surabaya. Employing a qualitative research design through a literature review method, data were gathered using observation, interviews, and documentation techniques. The findings reveal that implementing a cooperative Mind Mapping strategy fosters active student participation and encourages the development of collaborative skills, a sense of solidarity, and group responsibility. The subjects of this study were students at SD TAQUMA Surabaya. Furthermore, this strategy positively influences students’ learning motivation, as they feel more engaged and involved in the classroom process. Overall, the application of this method not only deepens students’ understanding of Islamic teachings but also supports the cultivation of religious character, piety, and the ability to embody moral values in everyday life.